Sexualidade na internet: a publicação em blogs de professores/as de ciências e biologia - Diniz, Gabriela Almeida (2015)
This work was developed within the Graduate Program in Education of the Federal University of Uberlândia - UFU, in the research area Education in Science and Mathematics. The question that motivated the research was: Which discourse about sexuality are in the publications of Biological Science teacher s blogs? Therefore, this study aimed: to locate teacher s blogs the area of Biological Sciences containing publications about sexuality; to verify the ways the authors of the selected blogs present publications related to sexuality; and to survey the discourses about sexuality crossing publications. The qualitative type research, considered the Science and Biology teacher s blogs as an investigative field, observing the constitution and identification of how sexuality is presented, and analyzing the wording of statements. In the investigation, we used methodological aspects of cultural analysis and Foucault\'s discourse analysis. From the blog survey several aspects were analysed: (i) the discourse of didactization of sexualitiy, (ii) the scientific discourse in dialogue with the media discourse, (iii) the discourse of health / disease and (ab)normality and (iv) the discourse of sex-gender-sexuality linearity. The analysis allowed approximations of contemporary strategies used to put into action the sexuality device in media spaces such as blogs in dialogue with new forms of subjectivity, of being of men and women.